Understanding the experiences of birthing care during COVID-19: A qualitative systematic review - Danielle Macdonald; Kristen Bigelow-Talbert; Amanda Ross-White; Erna Snelgrove-Clarke; Leah Sookhoo (International Journal of Nursing Studies Advances)
Background: The Covid-19 pandemic was a challenging time for people who sought health care and for health care providers. Throughout the pandemic women and birthing people, families, and health care providers adapted to ongoing changes, restrictions, and new information to ensure that babies were born safely. There was a strong policy focus on safety and the reduction of infection, however this focus did not account for how the changes to birthing care practice would influence the experiences of the people most continuously sharing space during birth – women and birthing people, midwives, and nurses. Objective: To explore and understand the birthing care experiences of women and birthing people, midwives, and nurses. Methods: We used the JBI methodology and methods to conduct our qualitative review. We included studies with participants who were women or birthing people, nurses, and midwives who received or provided birthing care during the Covid-19 global pandemic. Studies published between January 2020 and February 2023 were included. Studies had to report qualitative data. Results: A total of 5694 studies were identified for this review. After duplications were removed, screening and critical appraisal, 26 studies were included. Following meta-aggregation, 3 synthesized findings and 9 categories were created. The synthesized findings are 1) Navigating a pandemic and the chaos of constant changes 2) Striving for business as usual during a pandemic and 3) Amplifying variations in birthing care experiences. Conclusions: The experiences and needs of people who provide and receive birthing care must be prioritized in all spaces. Midwives, nurses, women, and birthing people must be included in decision making for changes to practices and policies at all levels, especially during uncertain times. Birth experiences must be respected and supported to ensure that health and wellness outcomes are optimized for families at all stages of the intrapartum, postpartum and early parenting journeys. Registration: Registered with Prospero CRD42021292832. An a priori protocol published, Macdonald, D., Snelgrove-Clarke, E., Ross-White, A., & Bigelow-Talbert, K. (2022). The experiences of birthing care during Covid-19: A systematic review protocol. JBI Evidence Synthesis. 20(5): 1353–1360. https://doi.org/10.11124/JBIES-21–00300